Regulating Global Business: The Economic Governance Potential of Corporate Codes of Conduct (European Journal of Marketing and Economics, 2025)
This study critically examines the evolving role of corporate codes of conduct as instruments of economic governance for multinational enterprises (MNEs) in an era of globalization. Through comparative analysis of 37 international regulatory initiatives—with particular focus on United Nations frameworks—the research identifies three persistent implementation gaps: (1) voluntary vs. binding compliance mechanisms (affecting 78% of existing codes), (2) jurisdictional conflicts in enforcement (noted in 63% of cases), and (3) economic incentive misalignment (reported by 56% of surveyed firms). The paper evaluates the OECD Guidelines and sector-specific charters through an economic governance lens, demonstrating how effective codes can reduce market failures by 22-35% when incorporating measurable compliance incentives. Case studies of Fortune 500 companies reveal that robust codes enhance foreign direct investment flows by 18-27% in developing markets while improving stakeholder confidence indices by 32-41 points. The analysis develops a novel compliance matrix assessing four economic dimensions: competitive equity (addressed in only 29% of current codes), supply chain accountability (43%), fiscal transparency (37%), and sustainable investment (51%). The findings support a policy framework where economically-calibrated codes complement traditional legal measures, proposing twelve actionable standards to strengthen transnational corporate governance.
Keywords: transnational corporations, corporate codes of conduct, global economic governance, compliance incentives, OECD Guidelines, UN frameworks, responsible business conduct, regulatory effectiveness